PENGAWASAN ANGKUTAN BARANG DI KOTA DUMAI - Hany Amalia; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
All of freight transport in Dumai sometimes make result traffict jum, accident and road damage. And then, author lift this theme for make change, like make safety, comfort and dicipline in driving.In this theme, author use UKAS theory. Dumai transportasion agency and police unit as informant in this study. Author use descriptive qualitative with data collection techniques throught observation, interview with informant and documentation.The result of this study of freight transport in Dumai City signify. Result obtained average but author get kind of deviations as conducted from field supervisors and much drivers. Factors of deviations among human resorces, availabilities of founds and awareness of drivers. The all of factor very important to implementation of better transport control in Dumai City.Keywords: Monitoring, Freight Transport